Weed Management in Cardamom Plantations - Sudheesh M V (Department of Agronomy, College of Horticulture, 1996)
A study was conducted during 1995 -96 to develop weed management practices for cardmom at Cardamom Research Station, Pampadumpara under Kerala Agricultural university. A trial was also conducted to evaluate major herbicides in cardamom plantions. Ten major weeds Ageratum conyzoides,Bidens pilosa, Crassocephalam crapioides, synedrella nodiflora, Paspalam conjugatum, Scoporia dulcis, Drymaria cordata, Erigeron Canadensis, Spilanthes calva and Eleusine indica were identified. Survey indicated the dominance of Asteraceae and Gramineae in cardamom tracts of Idukki district. Maximum germination percentage was observed in Bidens pilosa. All the weeds except Bidens pilosa, Scoparia dulcis and Spilanthes calva flowered in May. Rest of the weeds flowered by July and set seeds by the end of September. Maximum seed production and lowest 1000 seed weight was recorded by Scoparia dulcis. Nutrient study revealed the deversion of nutrients to flower heads after flower production. The results of the yield trial to compare efficiency of herbicides revealed the use of paraquat 0.4 kg/ha (bimonthly) or glyphosate 0.8 kg/ha is superior in terms of reducing the weed count, weed dry matter and nutrient removal by weeds from the experimental plots. Except tiller production all the characters, plant height (cm), per cent flowering (%) and yield (Kg/ha) did not differ significantly with treatments. Phytotoxic study revealed paraquat as less toxic than glyphosate. In combination with paraquat, atrazine and diuron residues persisted upto 60 days in the experimental field. More than rupees 6000 can be saved by adopting chemical methods instead of hand weeding.